THE EFFECT OF TOURISM MEDIA ON THE SUSTAINABLE TOURISM: APPLICABLE STUDY IN IRAQI BOARD OF TOURISM - Abbas Azeez, Zuhier (International Journal of Psychosocial Rehabilitation, 2020)
The effect of media that playing the various aspects of life is becoming increasingly greater day by day, especially in spheres like tourism and social interaction, and cultural and educational aspects of our life. So the development in communication is one of the best ways to go in developing the tourism which need a strategy that involves a planned communication component of programmers designed to change the attitudes and behavior of specific groups of people in specific ways through person to person communication, mass media, traditional media or community communication.